Legal Compliance of Education Providers Against Article 53 Paragraph (1) of Law No. 20 of 2003 Concerning the National Education System (Case Study: M3 Vocational High School) - Simamora, Cici Paramitha; Songgirin, Amin (Yayasan Sinergi Kawula Muda, 2023)
Article 53 paragraph 1 of the 2003 law concerning the National Education System is the absence of compliance caused by internal foundation conflicts so that legal compliance is legal compliance with Education Providers Against Article 53 Paragraph (1) of Law No. 20 Year drafted by Soerjono Sukamto related to Compliance, identification , internalization is not described at all related to SMK M3. Legal compliance was not carried out due to a foundation conflict which has also not received legal certainty to date. The problem in this thesis is how the M3 Vocational High School's Legal Compliance Against Article 53 Paragraph (1) Law No. 20 of 2003 Concerning the National Education System What is the legal standing of M3 Vocational High School Against Article 53 Paragraph (1) Law No. 20 of 2003 concerning the National Education. The research method used is research on the legal standing of the M3 Vocational High School against Article 53 Paragraph (1) of Law No. 20 of 2003 concerning the National Education System. The research method used is empirical research using field data. Data analysis was carried out in a qualitative normative way. The results of the study show that the government's indecisiveness towards educational institutions that do not use legal entities is of course based on history, meaning that this M3 school was founded before the foundation conflict was not a new school establishment. According to the author, the government also prioritizes students' rights in pursuing education and indirectly private schools are schools that assist the government in educating the nation's children.